Significantly Enhanced Electrochemical Redox for High‐Performance Electrochemical Capacitor via Active Ion‐Tunnel Oriented BaCoF4 Electrodes. Issue 13 (1st March 2021) - Guo, Changjin; Xie, Jiyang; Wang, Jing; Li, Lun; Zhu, Zhu; Xie, Lin; Mao, Yongyun; Hu, Wanbiao
Abstract: Active plane and specific morphology with reduced particle sizes have long been considered a promising strategy to achieve superior electrochemical properties, but the active sites involved may not be sufficiently utilized or the surface atomic configurations may obscure the activity. Herein, a novel structural "active orientation" strategy is developed to overcome the aforementioned shortcomings and improve the efficiency at active sites. A transition‐metal fluoride BaCoF4 is well controlled to thin the dimensions along an active [ 3 1 ¯ 0 ] orientation through a sodium dodecyl benzene sulfonate assisted solution chemistry route. The active orientation facilitates the opening of the ionic pathways, for example, OH – in the electrolyte, to take full advantage of the redox activity of the electrochemically active Co 2+ /Co 3+ cations in [ 3 1 ¯ 0 ] ‐BaCoF4, resulting in significantly enhanced electrochemical redox performance. A high specific capacitance (692 F g −1 at 1 A g −1 in 6 m KOH electrolyte) is achieved owing to active‐tunnels orientation, ≈five‐fold higher compared to its bulk counterpart. Strikingly, the asymmetric electrochemical capacitor (AEC) fabricated with [ 3 1 ¯ 0 ] ‐BaCoF4 and activated carbon exhibits an ultrahigh energy density of 147.7 Wh kg −1 at a power density of 1.025 kW kg −1 (also >100 Wh kg −1 at 5 kW kg −1 ), much higher than the majority of existing AEC systems. Abstract : A novel structural "active orientation" strategy is developed to sufficiently utilize the active sites via controlling over the active ion tunnels in BaCoF4 . The [ 3 1 ¯ 0 ] ‐oriented BaCoF4 based asymmetric electrochemical capacitor (AEC) exhibits an ultrahigh energy density of 147.7 Wh kg −1 at 1.025 kW kg −1 that is superior to a majority of existing AEC systems.